The Effect of Toxoplasma Gondii on DNA SequenceAlteration among BreastCancer Patients - Mohammed, nazar (Iraqi National Journal of Nursing Specialties, 2017)
Objective: The study aims to determine the effect of Toxoplasma gondii infection on thegenetic sequence of breast cancer patients in the Medical City Hospital – Tumor Unit /Iraq-Baghdad.Methodology: A study was carried out in the City of Medicine / Oncology Unit / Baghdad,during the period 1st June 2016 to 15th March 2017. Forty samples of tissue and serumwere collected from patients who complaining from Breast cancer and infected withToxoplasmosis. Forty sera samples were taken from patients complaining from parasiticinfection only; without breast cancer as control group. Data is analyzed by using ofdescriptive and inferential data analysis methods.Results: The results show that there is an effect for Toxoplasma gondii on the geneticsequence of patients complaining breast cancer, with significant differences among cancerpatients with Toxoplasmosis in comparison with negative toxoplasmosis control group.Recommendations: In view of the results, it is of importance to throw light on the geneexpression using real-time technique to detect the genetic mutation and the change in theprotein synthesis of patients with Toxoplasmosis